2020
DOI: 10.12659/ajcr.927137
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Plasminogen Activator-Induced Angioedema Involving a Posterior Cerebral Artery Infarct: A Case Presentation

Abstract: Patient: Female, 84-year-old Final Diagnosis: Angioedema Symptoms: Angioedema Medication:— Clinical Procedure: — Specialty: Critical Care Medicine • General and Internal Medicine Objective: Unusual clinical course Background: Angioedema is characterized by localized swelling of subcutaneous or submucosal tissue resulting from fluid extravasation due to the loss of vascular inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
(13 reference statements)
0
3
0
2
Order By: Relevance
“…Plasmin, on the other hand, influences the bradykinin production, resulting in angioedema (Figure 2). 66 There are multiple reports about the potential life‐threatening orolingual manifestation 67–70 . A study from the UK reported an 8% incidence of this side effect, ranging from 5 to 189 min after initiation of TPA.…”
Section: Other Causes Of Drug‐induced Bradykinin‐mediated Angioedema ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmin, on the other hand, influences the bradykinin production, resulting in angioedema (Figure 2). 66 There are multiple reports about the potential life‐threatening orolingual manifestation 67–70 . A study from the UK reported an 8% incidence of this side effect, ranging from 5 to 189 min after initiation of TPA.…”
Section: Other Causes Of Drug‐induced Bradykinin‐mediated Angioedema ...mentioning
confidence: 99%
“…66 There are multiple reports about the potential life-threatening orolingual manifestation. [67][68][69][70] A study from the UK reported an 8% incidence of this side effect, ranging from 5 to 189 min after initiation of TPA. Other authors reported slightly smaller incidences.…”
Section: Tissue Plasminogen Activator (Tpa)mentioning
confidence: 99%
“…Plasmin wiederum beeinflusst die Bradykinin‐Produktion, was zur Angioödem‐Entstehung führen kann (Abbildung 2). 65 Es gibt mehrere Berichte über die potenziell lebensbedrohliche orolinguale Manifestation 66–69 . In einer Studie aus dem Vereinigten Königreich wurde über eine Häufigkeit dieser Nebenwirkung von 8 % berichtet, die zwischen 5 und 189 Minuten nach Beginn der TPA‐Behandlung lag.…”
Section: Andere Ursachen Medikamenteninduzierter Bradykinin‐vermittel...unclassified
“…65 Es gibt mehrere Berichte über die potenziell lebensbedrohliche orolinguale Manifestation. [66][67][68][69] In einer Studie aus dem Vereinigten Königreich wurde über eine Häufigkeit dieser Nebenwirkung von 8 % berichtet, die zwischen 5 und 189 Minuten nach Beginn der TPA-Behandlung lag. Andere Autoren berichteten über etwas geringere Inzidenzen.…”
Section: Gewebeplasminogenaktivatorunclassified
“…[1] However, in addition to intracranial hemorrhage, Orolingual angioedema (OA) is a rare but potentially life-threatening complication is increasing. [2] OA presents as acute swelling of the tongue, lips, or face and can be life-threatening because it increases the risk of upper airway obstruction. [3] However, the mechanisms underlying RT-PA-induced OA remain unclear.…”
Section: Introductionmentioning
confidence: 99%